1993
DOI: 10.1111/j.1365-2273.1993.tb00810.x
|View full text |Cite
|
Sign up to set email alerts
|

Foreign body aspiration in children. The diagnostic value of signs, symptoms and pre-operative examination

Abstract: One hundred and fifteen patients, between 6 months and 12 years of age, had bronchoscopy on suspicion of foreign body aspiration. The histories of these patients were studied to examine the diagnostic value of signs, symptoms and examinations, and to determine the time that passed between aspiration and removal of the foreign body. The sensitivity of the symptoms choking and coughing was fairly high (81 and 78%), but the specificity was poor. The sensitivity of a chest radiograph was 82%, the specificity 44%. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
46
3
9

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 14 publications
5
46
3
9
Order By: Relevance
“…In our sample, the principal primary complication was pneumonia, as previously described in other Anatomically, the right bronchus, due to its greater verticality and larger diameter, favors the entry of a foreign body. (21) In the present study, we observed a predominance of the location of the foreign bodies were more often lodged in the right bronchus than in the left bronchus (54.8% vs. studies. (5,11,16) Procedure-related complications, such as barotrauma, occurred in only 2 patients.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In our sample, the principal primary complication was pneumonia, as previously described in other Anatomically, the right bronchus, due to its greater verticality and larger diameter, favors the entry of a foreign body. (21) In the present study, we observed a predominance of the location of the foreign bodies were more often lodged in the right bronchus than in the left bronchus (54.8% vs. studies. (5,11,16) Procedure-related complications, such as barotrauma, occurred in only 2 patients.…”
Section: Discussionmentioning
confidence: 54%
“…(15) This finding appears to have high specificity in FBA, (21,22) being present in more need for a second procedure in order to remove the foreign body (p < 0.05). In relation to the subsequent follow-up evaluation, 51 children were discharged from the hospital, and 18 (26%) returned as outpatients, the follow-up period ranging from 1 to 98 months (median, 3 months).…”
Section: Resultsmentioning
confidence: 97%
“…14 The sensitivity of a chest radiograph in diagnosis of FB aspiration is 82% and specificity 44%. 15 Chest radiography is the preferred initial investigation in cases of tracheobronchial FB aspiration. Unfortunately, almost 90% FBs are radioluscent and 30% of the chest radiographs inconclusive.…”
Section: Discussionmentioning
confidence: 99%
“…Aspirated foreign bodies may go unrecognised for prolonged periods of time, especially if the diagnosis is missed initially [91]. Foreign body aspiration is much more common in young males than in young females, and is especially frequent in children aged v4 yrs.…”
Section: Foreign Body Aspirationmentioning
confidence: 99%